The Influence of Sharia Marketing, Service Excellence, and Reputation on the Trust of Mudharabah Savings Customers (Case Study: BSI KCP Perbaungan) - Siagian, Siti Bejana; Rahma, Tri Inda Fadhila (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
Trust is one of the crucial factors in forming consumer loyalty because it is a form of consumer willingness to trust and rely on products and services. This study aims to analyze the influence of marketing Sharia variables. This study aims to analyze the influence of marketing sharia variables and service excellence on customer trust in mudharabah savings at BSI KCP Perbaungan. The sample used was 55 people and the method used in sampling was saturated sampling. Data was collected by distributing questionnaires to customers of mudharabah savings products. The analytical tool used is multiple linear regression analysis. The dependent variable of this study is customer trust. Independent variables include Sharia marketing, service excellence, and reputation. The research method used is quantitative. For data analysis method using multiple regression analysis models. While processing the data using SPSS. The results showed that from the variables that had been examined between the dependent and independent variables, the results of the research test using the multiple regression analysis models obtained the dependent variable customer trust in mudharabah savings that could be influenced by sharia marketing, service excellence, and reputation.